2019
DOI: 10.1371/journal.pone.0215125
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to pay for hepatitis B vaccination in Selangor, Malaysia: A cross-sectional household survey

Abstract: Background In Malaysia, one million individuals are estimated to be infected with the hepatitis B virus. A vaccine for infants has been compulsory since 1989, whereas those born before 1989 need to spend their own money to be vaccinated in private clinics or hospitals. The aim of this study was to investigate and ascertain the determinants of willingness to pay (WTP) for adult hepatitis B vaccine in Selangor, Malaysia. Methods In 2016, 728 households were selected throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
56
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 62 publications
(67 reference statements)
5
56
2
Order By: Relevance
“…One important finding is that those who had a higher perceived risk to be infected with COVID-19 were more likely to accept the vaccine, but only for the 95% effective vaccine. Previous studies in Asia have found that perceived risk or perceived susceptibility to an infection is associated with positive support for vaccination (29,30,39). Another study also found that high perceived risk was associated with COVID-19 vaccine acceptance among general community members in Saudi Arabia (40) and among HCWs in China (41).…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…One important finding is that those who had a higher perceived risk to be infected with COVID-19 were more likely to accept the vaccine, but only for the 95% effective vaccine. Previous studies in Asia have found that perceived risk or perceived susceptibility to an infection is associated with positive support for vaccination (29,30,39). Another study also found that high perceived risk was associated with COVID-19 vaccine acceptance among general community members in Saudi Arabia (40) and among HCWs in China (41).…”
Section: Discussionmentioning
confidence: 88%
“…In the region of southeast Asia, studies have been conducted to assess the acceptance of a vaccine against infectious diseases (21)(22)(23)(24)(25)(26)34). This present study was conducted to understand how the COVID-19 vaccine, when available, will be accepted by the general population in Indonesia, by asking individuals about a hypothetical vaccine-an approach used in many past studies (21,26,(28)(29)(30). Understanding vaccine acceptance in Indonesia is important, given the large population and because the country has relatively high vaccine hesitancy for existing vaccines and relatively low vaccination coverage (18,19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to previous studies conducted in Malaysia, the WTP for the hypothetical COVID-19 vaccine found in this study is over three-fold higher than the WTP for a hypothetical dengue vaccine (MYR39.21 [USD 9.45 USD] per dose) 19 and the hepatitis B vaccination (MYR$303 [USD 73 USD] per three-dose series). 20 To date, no studies have been conducted on the WTP of influenza vaccine in Malaysia. In Malaysia, influenza vaccination is not mandatory.…”
Section: Discussionmentioning
confidence: 99%
“…Though limited evidences are available on health professionals’ WTP for HBV vaccination, evidences are available on WTP for vaccinations against other viruses such as Dengue virus, Tick-borne Encephalitis virus, Influenza virus, and Zika virus. These evidences show that sex, age, marital status, educational status, occupation, monthly income, residence, knowledge and attitude towards the vaccine, time consumed, perceived risk, disease related knowledge, severity of the disease, peer pressure, and medical advice are factors associated with willing to pay for vaccination [2126].…”
Section: Introductionmentioning
confidence: 99%